Assessing Teacher Readiness for AI Utilization: Between Innovation Opportunities and Ethical Challenges in 21st-Century Learning - Nindigraha, Nunung; Firdaus, Kevin Herdinata Cahyadi; Prihatmoko, Yulias; Oktaviani, Herlina Ike (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
This study aims to analyze teachers’ readiness and ethical awareness in utilizing Artificial Intelligence (AI) for learning innovation in Indonesia, examining their perceptions of AI’s benefits and challenges, exploring its pedagogical applications, and developing a conceptual AI literacy framework for educators. Employing a quantitative descriptive design, the research involved 107 teachers across educational levels who completed an online survey using a 7-point Likert scale. Data were analyzed descriptively and comparatively, guided by the Technology Acceptance Model (TAM), Technological Pedagogical Content Knowledge (TPACK), and Diffusion of Innovation Theory. The findings indicate moderate technological readiness (M = 3.66; SD = 1.16) and positive perceptions of AI’s potential to enhance productivity and creativity in teaching (M = 3.8). AI is predominantly used for lesson planning (75.7%) and content development (64.5%), while its application in assessment remains limited (46.7%). Teachers demonstrate relatively high ethical awareness (M = 4.20; SD = 1.24) regarding data privacy, plagiarism, and algorithmic fairness, although a gap persists between ethical understanding and classroom practice. Major barriers include limited AI-specific training (68%), inadequate infrastructure (54%), and concerns about reliability and validity (49%). The study proposes an “AI Literacy Framework for Teachers” integrating technical, pedagogical, and ethical competencies, emphasizing the alignment of technological proficiency with moral reflection and humanistic values to support innovative and responsible learning.